2020
DOI: 10.1192/bjo.2020.118
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mindfulness-based cognitive therapy for major depressive disorder: evidence from routine outcome monitoring data

Abstract: Background Meta-analyses show efficacy of mindfulness-based cognitive therapy (MBCT) in terms of relapse prevention and depressive symptom reduction in patients with major depressive disorder (MDD). However, most studies have been conducted in controlled research settings. Aims We aimed to investigate the effectiveness of MBCT in patients with MDD presenting in real-world clinical practice. Moreover, we assessed whether guideline recommendations for MBCT allocation in regard to recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The most commonly used intervention for major depressive disorder was mindfulness‐based cognitive therapy (MBCT). Four articles—Geurts et al (2020); Schoenberg and Speckens (2015); Williams et al (2020); and Hanssen et al (2019)—introduced a standardized MBCT 8‐week program designed as a nonrandomized control trial and reported significant improvement in SC scores after intervention, compared to baseline. Schuling et al (2020) conducted a randomized controlled trial (RCT) using mindfulness‐based compassionate living (MBCL), which is a follow‐up to MBCT, aimed at cultivating compassion for patients who previously received MBCT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used intervention for major depressive disorder was mindfulness‐based cognitive therapy (MBCT). Four articles—Geurts et al (2020); Schoenberg and Speckens (2015); Williams et al (2020); and Hanssen et al (2019)—introduced a standardized MBCT 8‐week program designed as a nonrandomized control trial and reported significant improvement in SC scores after intervention, compared to baseline. Schuling et al (2020) conducted a randomized controlled trial (RCT) using mindfulness‐based compassionate living (MBCL), which is a follow‐up to MBCT, aimed at cultivating compassion for patients who previously received MBCT.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, changes in SC after follow‐up affected depression. Geurts et al (2020) reported that increased change in SC is negatively correlated with decreased changes in depression, before and after the MBCT intervention. Schuling et al (2020) reported that the reduction effects in depression after the MBCL intervention were moderated by SC, but not by rumination and mindfulness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness-based interventions (MBI) integrated the essence of traditional mindfulness practice with contemporary psychological practice and have recently gained much interest in the scientific world and in the therapy of depression (Hofmann et al, 2010;Gu et al, 2015;Segal and Walsh, 2016;Bulzacka et al, 2018;Cladder-Micus et al, 2018;Geurts et al, 2020;Ninomiya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For patients with recurrent unipolar depression, MBCT reduces both relapse (Kuyken et al, 2016) and severity of depressive symptoms (Geurts, Compen, et al, 2020;Goldberg et al, 2019;Strauss et al, 2014). In a systematic review, Lovas & Schuman-Olivier (2018) described MBCT as a promising treatment for patients with BD.…”
Section: Introductionmentioning
confidence: 99%